A FEMININE OF NO ONE’S OWN IN CHARLOTTE TÁBUA RASA - Eider Madeiros; Letícia Simões Velloso Schuler; Mariana Pinheiro Ramalho; Hermano de França Rodrigues (REVES - Revista Relações Sociais)
This paper aims to essay an open and constructive dialogue between the very rupture that the trans female body evokes and the recent concept of “feminine of no one”, through an inductive approach that the latter could make it possible to be kept in a state of infiniteness, of openness, of incompleteness, of non-wholeness, the aspect that characterizes the surrounding and expressive territories of each one of the specific bodies that allow themselves to be situated more leaned onto the feminine. Based on the contributions of Bento (2008), Jorge and Travassos (2018), from the brief precepts of Lacanian psychoanalysis, and on an interview with Leonardo Valente, the author of Charlotte Tábua Rasa (2016), we intend to discuss insofar how the body of a trans woman in a Brazilian politics fictional scenario would be able to draw the difficult boundaries on the discourses, possessions and the domains of language between the self and the other towards the trans-sexualities which dedicate their efforts to reinscriptions and the fissures that are celebrated through the transgressive resilience of the feminine.